2022
DOI: 10.3390/ijgi11030182
|View full text |Cite
|
Sign up to set email alerts
|

An Application of Improved MODIS-Based Potential Evapotranspiration Estimates in a Humid Tropic Brantas Watershed—Implications for Agricultural Water Management

Abstract: The reliance on native MODIS-16 PET potential evapotranspiration (PET) in scarce-data-driven areas is growing in support among ecohydrological studies, yet information about its performance is limited or unknown as validation studies are mostly concentrated in developed countries. This study aimed to assess its performance at the monthly level using four ground measurements in a tropical watershed system with complex topography, applying a machine learning artificial neural network (ANN) to improve the estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…However, climate change has a considerable influence on the agriculture sector, and it could lead to an increase in temperatures by 1.4 to 5.8 degrees Celsius in 2100 [4]. This will increase crop water requirements due to increased evapotranspiration, which will mainly affect crop production [63]. This study shows acceptable accuracy for crop yield prediction that can be used by policymakers for management at the country and province scales.…”
Section: Discussionmentioning
confidence: 95%
“…However, climate change has a considerable influence on the agriculture sector, and it could lead to an increase in temperatures by 1.4 to 5.8 degrees Celsius in 2100 [4]. This will increase crop water requirements due to increased evapotranspiration, which will mainly affect crop production [63]. This study shows acceptable accuracy for crop yield prediction that can be used by policymakers for management at the country and province scales.…”
Section: Discussionmentioning
confidence: 95%
“…More and more scientific work in the field of precision agriculture is focusing on the use of satellite data in the development of ML models. Data from Sentinel 1 and Sentinel 2 satellites [34,64], and the MODIS optical-mechanical scanner deployed on Terra and Aqua satellites [16,[65][66][67] are commonly used. These tools allow the collection of spectral and multispectral data, which are aids for calculating vegetation indices (VIs).…”
Section: Data and Sourcesmentioning
confidence: 99%
“…MODIS 16 evapotranspiration data are widely and commonly used, and Jovanovic et al (2015) found that MODIS 16 evapotranspiration and potential evapotranspiration estimates over South Africa's landscape were satisfactory; however they cautioned that the spatial resolution can limit its potential for small-scale use. Some studies have argued that MODIS 16-derived PET is suited for small-scale application (Astuti et al, 2022). Bugan et al (2020) utilised the MODIS 16 dataset in a hydrological model at a catchment level and concluded that the dataset has the potential to be used in data-scarce regions.…”
Section: Remote Sensing Datamentioning
confidence: 99%